2022
DOI: 10.37256/jspr.1120221140
|View full text |Cite
|
Sign up to set email alerts
|

Envisioning Change: An Empirical Test of the Social Psychological Model of Utopian Thinking and Collective Action

Abstract: This article provides the first empirical evidence of the theoretical model by Badaan et al. (2020) that proposes social psychological mechanisms whereby utopian thinking, which activates the social imagination, could enhance collective action intentions geared toward progressive social change. We anticipated that imagining better societies via utopian thinking would (a) increase social hope, (b) promote an abstract mindset that bridges psychological distance between the status quo in the present and the imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…In contrast to the majority, who wanted to create a new society based on their values, only few participants stated that their primary motivation was to re‐establish the pre‐pandemic society. In line with recent research (Badaan et al., 2022), this finding suggests that utopian thinking about the potential of a highly idealised future might have encouraged protesting. One reason might be that utopian thinking provides an avenue of hope that encourages efficacy perceptions and therefore increases protesters’ likeliness to participate (Badaan et al., 2020).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…In contrast to the majority, who wanted to create a new society based on their values, only few participants stated that their primary motivation was to re‐establish the pre‐pandemic society. In line with recent research (Badaan et al., 2022), this finding suggests that utopian thinking about the potential of a highly idealised future might have encouraged protesting. One reason might be that utopian thinking provides an avenue of hope that encourages efficacy perceptions and therefore increases protesters’ likeliness to participate (Badaan et al., 2020).…”
Section: Resultssupporting
confidence: 87%
“…Thus, our analysis demonstrates the value of integrating temporal extensions into the SIMCA model to get a more holistic understanding of people's motivation to engage in collective action, as suggested recently (e.g. Badaan et al., 2022; Freel & Bilali, 2022; Power, 2020). Integrating social‐identity‐based and cultural‐historical‐based approaches, such as those illustrated in Figure 3, can help unravel the psychology of collective action, also outside the present study's focus on anti‐containment measures.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Indeed, emerging research supports this conjecture: Fernando et al (2018) reported that inducing participants to think about their version of an ideal society increased motivation to take action for social change. Similarly, Badaan et al (2022) found that reading a text about a utopian society elicited greater hope, which in turn predicted intentions to engage in collective action for social change.…”
mentioning
confidence: 94%
“…Collective action is a popular research field that originates from the assessment of protest movements. It is by now widely applied across disciplines such as psychology (e.g., van Zomeren et al, 2008;Jost et al, 2017;Badaan et al, 2022;Galesic et al, 2022), political sciences (e.g., Ostrom, 1990Ostrom, , 2009Jagers et al, 2020), sociology (e.g., .…”
Section: Introductionmentioning
confidence: 99%